Sex differences in associations of socioemotional dispositions measured in childhood and adolescence with brain white matter microstructure 12 years later - Benjamin B. Lahey; Kendra E. Hinton; Francisco Calvache Meyer; Victoria Villalta-Gil; Carol A. Van Hulle; Brooks Applegate; Xiaochan Yang; David H. Zald (Personality Neuroscience, 2020)
Predictive associations were estimated between socioemotional dispositions measured at 10–17 years using the Child and Adolescent Dispositions Scale (CADS) and future individual differences in white matter microstructure measured at 22–31 years of age. Participants were 410 twins (48.3% monozygotic) selected for later neuroimaging by oversampling on risk for psychopathology from a representative sample of child and adolescent twins. Controlling for demographic covariates and total intracranial volume (TICV), each CADS disposition (negative emotionality, prosociality, and daring) rated by one of the informants (parent or youth) significantly predicted global fractional anisotropy (FA) averaged across the major white matter tracts in brain in adulthood, but did so through significant interactions with sex after false discovery rate (FDR) correction. In females, each 1 SD difference in greater parent-rated prosociality was associated with 0.43 SD greater FA (p < 0.0008). In males, each 1 SD difference in greater parent-rated daring was associated with 0.24 SD lower FA (p < 0.0008), and each 1 SD difference in greater youth-rated negative emotionality was associated with 0.18 SD greater average FA (p < 0.0040). These findings suggest that CADS dispositions are associated with FA, but associations differ by sex. Exploratory analyses suggest that FA may mediate the associations between dispositions and psychopathology in some cases. These associations over 12 years could reflect enduring brain–behavior associations in spite of transactions with the environment, but could equally reflect processes in which dispositional differences in behavior influence the development of white matter. Future longitudinal studies are needed to resolve the causal nature of these sex-moderated associations.